Effectiveness of Parental Nutrition Education Intervention in Prevention and Handling of Undernutrition in Toddlers: Literature Review - Azkia, Bardiatul; Setiarini, Asih (Mandalika Institute, 2025)
Malnutrition in children is still a public health problem in various countries, especially low- and middle-income countries, especially the problem of undernutrition (wasting, stunting, underweight). Specific nutritional intervention strategies are needed to improve the nutritional status of children under the age of five. This literature review study was conducted to summarize various nutritional education interventions that have been carried out in the last 3 years and their relationship to improving knowledge and nutritional status of toddlers. The literature search was sourced from various electronic databases (ProQuest, Science Direct, and Springer Link). The type of research used in this literature review is experimental research so that the differences in the effects of the nutritional education interventions carried out can be seen. The main results obtained are that nutritional education has an effect on increasing the knowledge of mothers and caregivers of toddlers regarding the necessary nutritional science and also has an effect on the average z-score and even reducing the number of malnutrition. Providing adequate additional food can strengthen the positive impact on improving the nutritional status of toddlers which runs linearly with the provision of nutritional education. Nutrition education also has an effect on increasing knowledge of the importance of monitoring growth and food diversity at the household level which also has an indirect effect on the nutritional status of toddlers. Nutrition education can be done with several methods and nutritional content according to needs and targets. More nutritional education interventions are needed with appropriate adjustments to methods, needs, and targets as an effort to prevent and reduce malnutrition rates in toddlers.